The Acute and Sub-Chronic Toxicological Evaluation of n-Hexane Fraction of Uvaria chamae Leaves - ayorinde, odunayo, E.D, Manuel-Mosi; O.O., Fayehun; J.I, Olawuni; E., Ogunwole; C.A, Elusiyan, G, Olayiwola (African Journal of Infectious Diseases (AJID), 2025)
Background: The plant species identified as Uvaria chamae, a member of Annonaceae has exhibited notable biological effect in in-vivo studies. However, a comprehensive toxicity profile is essential to assess the safety of U. chamae for potential therapeutic applications. This research investigated the toxicity U. chamae leaves (n-hexane fraction) in order to identify any potential adverse effects and establish a safer dosage threshold for prolonged use. Methods: The n-hexane partitioned fraction obtained from U. chamae leaves was subjected to acute and sub-chronic toxicity evaluations. The short-term toxicity assessment followed established procedures. For the sub-chronic study, a total of 30 animals received the fraction continuously for 35 days. Biochemical analyses were performed on serum and liver homogenates to assess key parameters, including Aspartate aminotransferase (AST) and Alanine aminotransferase (ALT), Triglycerides (TRIG) and Total cholesterol (TC). Also, histopathological examinations were performed on selected tissue samples. Results: The acute toxicity assessment showed an LD₅₀ value exceeding 5000 mg/kg. For the repeated dose toxicity study, results showed statistically significant effect (p < 0.05) variations in AST and ALT levels within both liver and serum homogenates in relation to dosage. Additionally, histopathological analysis identified morphological alterations that distinct from the control group and consistent with those typically observed in damaged tissues. Conclusion: At high dosages, the acute toxicity evaluation revealed that the U. chamae (n-hexane partitioned fraction) was non-toxic. On the other hand, prolonged administration led to significant biochemical and morphological alterations. A dose below 200 mg/kg is a suggested safer threshold when considering extended use.